Lightweight climate models could be useful for assessing aviation mitigation strategies and moving beyond the CO2-equivalence metrics debate - Sara Arriolabengoa; Thomas Planès; Philippe Mattei; Daniel Cariolle; Scott Delbecq (Communications Earth & Environment)
Abstract Assessing mitigation strategies for aviation is a critical issue for the aviation stakeholders, while the debate continues on the most appropriate CO2-equivalence metrics to address non-CO2 effects. Here, we propose two lightweight climate models that can be parameterised to assess these strategies and move beyond the CO2-equivalence metrics debate. A first approach relies on the use of the GWP* method, while a second one uses the FaIR climate emulator. These lightweight models, which should be considered as a new family of climate models for aviation that facilitate parametric studies, provide a straightforward and consistent means of evaluating mitigation strategies at the temperature level, although they are still limited for informing policymakers due to the significant uncertainties involved. They bypass the need for CO2-equivalence metrics for comparing strategies. The latter should rather be used for other applications, such as policy mechanisms to encourage the emergence of strategies, as they are not suitable for assessing temperature changes from aviation. The debate on the choice of CO2-equivalence metrics could then focus on methodological and ethical criteria. However, this paper demonstrates that the higher the traffic, the more appropriate it is to choose CO2-equivalence metrics with high values for consistency with temperature estimates.